2013
DOI: 10.1080/00014788.2013.827105
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising disclosures in the annual report

Abstract: Drawing upon information economics, this paper presents a relative assessment of 24 of the most common disclosure items in the management commentary and notes sections of the annual report. We design and conduct an Internet survey using a large representative sample of users with an investment focus (n ¼ 288) and preparers of annual reports (n ¼ 89). Using cost-effectiveness analysis, an evaluation method widely used in healthcare economics, the balance between preparation costs and user satisfaction, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
(59 reference statements)
2
29
0
3
Order By: Relevance
“…The analysts' responses to this question suggest that preparers may increase user satisfaction by making their existing disclosures less generic and more company specific. Given that concerns about the high cost of financial instruments disclosures have been identified (Johansen and Plenborg 2013), our research may serve to alleviate those concerns. Our interviews with analysts revealed little demand for nonbanks to increase quantitative disclosure or undertake more advanced modelling that would be complex and therefore costly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysts' responses to this question suggest that preparers may increase user satisfaction by making their existing disclosures less generic and more company specific. Given that concerns about the high cost of financial instruments disclosures have been identified (Johansen and Plenborg 2013), our research may serve to alleviate those concerns. Our interviews with analysts revealed little demand for nonbanks to increase quantitative disclosure or undertake more advanced modelling that would be complex and therefore costly.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of users are quite sparse and tend to provide more information about investors than lenders (see Beattie and Pratt 2002). However, in one recent study, Johansen and Plenborg (2013) provided evidence on the usefulness of 24 mandatory disclosures, including IFRS 7, by surveying 288 users (private investors, professional investors, sell-side analysts and bank analysts) and 89 companies (small, medium, large and state-owned) to obtain their views. They reported that IFRS 7 disclosures are highly demanded by all categories of user, that these are also among the items thought by companies to be most costly to prepare, and that users are comparatively less satisfied with these notes.…”
Section: Ifrs 7 Usefulness Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The studies including Al-Mubarak (1997), Al-Gareh (2001), Al-Fayyoumi (2003), Abuzarour (2005), Abdelkarim and Shahin (2007), and Abdelkarim, Shahim, and Arqawi (2009) focus on the investors' assessment of the information provided by the business. Johansen and Plenborg (2013) evaluated the level of priority in the publication of information on the financial statements of the companies in Denmark. Similarly, the annual professional organizations have surveys to assess the quality of information in the financial statements of the enterprises such as International Federation of Accountants (IFAC, 2013), ICAEW (2014), etc..…”
Section: The Previous Study and Hypothesis Developmentmentioning
confidence: 99%